Destruction of self-derived PAMP via T3SS2 effector VopY to subvert PAMP-triggered immunity mediates Vibrio parahaemolyticus pathogenicity - Xuan Wu; Lantian Zhou; Chen Ye; Zhenzhong Zha; Chuchu Li; Chao Feng; Yue Zhang; Qian Jin; Jianyi Pan (Cell Reports, 2023)
Summary: Cyclic di-guanosine monophosphate (c-di-GMP) is a unique bacterial second messenger but is hijacked by host cells during bacterial infection as a pathogen-associated molecular pattern (PAMP) to trigger STING-dependent immune responses. Here, we show that upon infection, VopY, an effector of Vibrio parahaemolyticus, is injected into host cells by type III secretion system 2 (T3SS2), a secretion system unique to its pathogenic strains and indispensable for enterotoxicity. VopY is an EAL-domain-containing phosphodiesterase and is capable of hydrolyzing c-di-GMP. VopY expression in host cells prevents the activation of STING and STING-dependent downstream signaling triggered by c-di-GMP and, consequently, suppresses type I interferon immune responses. The presence of VopY in V. parahaemolyticus enables it to cause both T3SS2-dependent enterotoxicity and cytotoxicity. These findings uncover the destruction of self-derived PAMPs by injecting specific effectors to suppress PAMP-triggered immune responses as a unique strategy for bacterial pathogens to subvert immunity and cause disease.